Enhanced microalgal lipid production for biofuel using different strategies including genetic modification of microalgae: a review - Khoo, Kuan Shiong (2023)
Microalgae have gained considerable attention as an alternative feedstock for the biofuel production, particularly in combination with genetic modification strategies that target enhanced lipid productivity. To tackle climate change issues, phasing out the usage of fossil fuels is seen as a priority, where the utilization of biofuel from microalgae serves as a potential sustainable energy source for various applications. These photosynthetic microalgae utilize solar energy and carbon dioxide to produce energy-rich compounds (i.e., starch and lipids), that can be further converted into biofuels of different types. Among different types of biofuels, biodiesel from the transesterification of triacylglycerols stands out as the most sustainable replacement of transportation fuel over fossil-based petroleum diesel. However, hurdles such as limited productivity, overall production cost and challenges in upscaling the algal technology leaves a huge gap on the road to commercialized microalgae-based biofuel. This review article first presents a comprehensive overview of imperative knowledge regarding microalgae in terms of algal classification, factors affecting the growth of microalgae during cultivation and different steps in upstream processing. This review also discusses recent advances in downstream processing of microalgal biorefinery. Additionally, this review paper focuses on deliberating various recent strategies of genetic modifications and their feasibility for enhanced lipid productivity in microalgae. Finally, the current challenges and future perspectives of microalgae-based biofuels are highlighted in this review discussing several aspects, including sustainability of microalgae-based biofuel production, current status of algae-based industry, risks and legislation considerations of genetic modification of microalgae.